A residual strain model for progressive fatigue damage analysis of composite structures. (1st June 2017) - Zhao, Libin; Shan, Meijuan; Hong, Haiming; Qi, Dexuan; Zhang, Jianyu; Hu, Ning
Abstract: A residual strain model was presented based on the fatigue-accumulated damage mechanisms of composite materials. By combining the proposed residual strain model with a residual stiffness model, the gradually degraded material properties due to the damage in fatigue cycles were characterized. Accompanying the residual strain based gradual material degradation model with a micromechanics-based sudden material degradation rule for describing the stiffness degradation in one fatigue cycle and an extended maximum strain criterion for evaluating failure of materials, a progressive fatigue damage model (PFDM) of a typical double-lap three-bolt joint made of T800 carbon/epoxy composites was developed. Compared with the residual strength model in a traditional PFDM, the residual strain model has consistent parameters with those in the residual stiffness model, which could be determined by nondestructive experiments. Fatigue tests of the double-lap three-bolt joint specimens under a stress ratio R = −0.2 and three-level load ratios q = 0.7, 0.8, 0.9 were performed. Good consistency between the experimental results and numerical predictions of the PFDM validates the efficiency of the proposed residual strain model and PFDM in accurately predicting the residual strength and fatigue life of composite structures.